2003
DOI: 10.1007/s00464-002-9088-z
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic treatment of simple hepatic cysts and polycystic liver disease

Abstract: Laparoscopic fenestration could be the preferred treatment of solitary liver cysts and PLD. Adequate selection of patients and type of cystic liver together with a meticulous surgical technique are recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
1
14

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(76 citation statements)
references
References 19 publications
2
59
1
14
Order By: Relevance
“…Drenth et al [4] reported a recurrence rate of 24%, complication rate of 22%, and mortality rate of 2% in 311 patients. Recently, laparoscopic fenestration has been increasingly reported, but the complication and recurrence rates are similar to those caused by open fenestration [4,5], and sufficient evaluation is necessary for its application.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drenth et al [4] reported a recurrence rate of 24%, complication rate of 22%, and mortality rate of 2% in 311 patients. Recently, laparoscopic fenestration has been increasingly reported, but the complication and recurrence rates are similar to those caused by open fenestration [4,5], and sufficient evaluation is necessary for its application.…”
Section: Discussionmentioning
confidence: 99%
“…Fenestration is less invasive than hepatectomy, and, recently, it has been found that the procedure may be performed laparoscopically. The most frequent perioperative complication is ascites, the incidence of which is 24%, and the recurrence rate has been reported to be 20% [4,5]. …”
Section: Introductionmentioning
confidence: 99%
“…A cystadenocarcinoma is a malignant neoplasm and therefore resection is the definitive management. Due to their potential for malignant transformation, formal resection is also advised for cystadenomas [1,4,21,22]. Four of our patients were asymptomatic leading up to surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Mit zunehmender Größe der Zyste steigen jedoch die Rezidivquote, die Anzahl der nötigen Injektionen und damit die Komplikationsrate [2]. Die chirurgische Behandlung (laparoskopisches "unroofing") zeigt eine Rezidivrate von 0-15% [3] sowie eine Morbidität von bis zu 25% [4,5]. Komplikationen sind u.a.…”
Section: Fallbeschreibungunclassified